Saltwater fish consumption pattern and incidence of hypertension in adults: A study on the population of Gresik coast, Indonesia - Umdatus Soleha; Mochammad Bagus Qomaruddin (SAGE Publishing, 2020)
Background: Hypertension is one of the main causes of morbidity and mortality in the Indonesian population, characterized by an increasing number of sufferers each year. Curtailing saltwater fish consumption pattern is an optional effort to prevent hypertension, as most users tend to attribute little or no attention to this possibility. Design and Methods: The purpose of this study, therefore, was to analyze the correlation between saltwater fish consumption pattern and the incidence of hypertension in adults, using analytic research design with cross sectional approach. Results: The analysis showed the dominance of female respondents (63%), aged 36-45 years (60%), graduated from senior high school (33.8%), working as housewives (32.5%), monthly income above the average (63.6%), absence of hypertension history (80.5%), eat sea fish often as a side dish (59.7%), and pre hypertension (59.1%). Furthermore, data analysis showed a Pvalue of 0.000, indicating the presence of a significant relationship between the consumption pattern of sea fish and the incidence of hypertension. Conclusions: The results of this study show the high consumption of saltwater fish by most people living in Kebungson, Gresik Village. This correlates with the incidence of hypertension in indigenous adults, as the majority was classified with prehypertension levels.